Manganese-enhanced MRI of salivary glands and head and neck tumors in living subjects - Seshadri, Mukund; Hoy, Allison (Magnetic resonance in medicine, 2010)
Manganese‐enhanced MRI has previously been used for visualization of brain architecture and functional mapping of neural pathways. The present work investigated the potential of manganese‐enhanced MRI for noninvasive imaging of salivary glands in living subjects. Marked shortening of T1 was observed in salivary glands of naïve mice (n = 5) 24–48 h after systemic administration of MnCl2 (0.4 mmol/kg, intraperitoneally). Three‐dimensional MR microscopy confirmed selective contrast enhancement of salivary gland tissues post–MnCl2 injection. Ectopic and orthotopic head and neck tumor xenografts also showed an increase in R1 at 24 h following MnCl2 injection (0.2 mmol/kg, intraperitoneally). However, tumor enhancement was minimal compared to salivary gland tissue. Salivary gland R1 values were lower in mice bearing orthotopic head and neck tumors compared to naïve mice. These results demonstrate, for the first time, the usefulness of manganese‐enhanced MRI in the visualization of salivary glands and head and neck tumors in vivo. Magn Reson Med, 2010. © 2010 Wiley‐Liss, Inc.